2008
DOI: 10.4049/jimmunol.180.5.2747
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TNFR-Shedding by CD4+CD25+ Regulatory T Cells Inhibits the Induction of Inflammatory Mediators

Abstract: CD4+CD25+ regulatory T (Treg) cells play an essential role in maintaining tolerance to self and nonself. In several models of T cell-mediated (auto) immunity, Treg cells exert protective effects by the inhibition of pathogenic T cell responses. In addition, Treg cells can modulate T cell-independent inflammation. We now show that CD4+CD25+ Treg cells are able to shed large amounts of TNFRII. This is paralleled by their ability to inhibit the action of TNF-α both in vitro and in vivo. In vivo, Treg cells suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 21 publications
7
101
0
1
Order By: Relevance
“…Accordingly, TNF impairs the function of Treg cells, which are potent suppressors of osteoclast formation, and TNF blockade might reverse this effect (57). This is also supported by the observation that Treg cells shed TNF receptors and might thus block TNF-induced osteoclastogenesis (58). Based on these multiple effects on osteoclast differentiation and activity, it is conceivable that TNF-blocking therapy strongly inhibits bone erosions in the joints of patients with active RA, since these lesions are a direct consequence of osteoclast formation.…”
Section: Tnf Blockadesupporting
confidence: 52%
“…Accordingly, TNF impairs the function of Treg cells, which are potent suppressors of osteoclast formation, and TNF blockade might reverse this effect (57). This is also supported by the observation that Treg cells shed TNF receptors and might thus block TNF-induced osteoclastogenesis (58). Based on these multiple effects on osteoclast differentiation and activity, it is conceivable that TNF-blocking therapy strongly inhibits bone erosions in the joints of patients with active RA, since these lesions are a direct consequence of osteoclast formation.…”
Section: Tnf Blockadesupporting
confidence: 52%
“…Therefore, the functionally relevant activation of Tregs in vivo may depend on the availability of either TNF-a or TGF-b, and the requirement for TGF-b in iTreg generation may concomitantly lessen or remove the requirement for TNF-a to achieve maximal function of iTregs. It has been reported previously that TNFR2 2/2 nTregs are able to suppress normally in vitro (14). In this study, we find no phenotypic differences between WT and TNFR2 2/2 nTregs that would account for the abnormal in vivo function of TNFR2 (19) showing that TNF-a is necessary for optimizing, or "boosting," Treg function in the context of autoimmunity, rather than being required for the baseline functioning of Tregs.…”
Section: Preactivation Of Tnfr2mentioning
confidence: 37%
“…In mice, TNF-a has been reported to stimulate in vitro Treg proliferation and suppressive function (10), and it has been suggested that expression of TNFR2 defines a maximally suppressive subset of Tregs in both mice and humans (11)(12)(13). In addition, shedding of soluble TNFR2 by murine nTregs has been reported to block the proinflammatory effects of TNF-a (14). In contrast, it has been shown in humans that TNF-a decreases the in vitro suppressive function of both CD4 + CD25…”
mentioning
confidence: 99%
“…-FOXP3 + Tregs express higher levels of TNFR2 compared with other T cell subsets Previous studies (4,19) show that at homeostasis blood-derived CD4 +…”
Section: Cd45ramentioning
confidence: 99%
“…Previous studies using the in vitro coculture suppression assay suggest that exogenous soluble TNF can inhibit the human Treg suppressive function (4,19). To further investigate the functional consequences of TNF treatment on Tregs in our system, we cocultured freshly isolated CD25 + Tregs with CFSE-labeled CD25 -Tcons at various ratios.…”
Section: Tnf/tnfr2 Signaling Modulates the Treg Suppressive Functionmentioning
confidence: 99%